THE CONCEPT OF BUDDHIST PHILOSOPHY FOR ELDERCARE - Iyara, Wichai; bhavanaphodhikun, Prakru; Leeka, Jaras; Sutassanavipani, Phramahanatthabhan; Siridhammo, Phramaha Paitoon; เทวธมฺโม, พระยงค์ยุทธ (Journal of Graduate MCU KhonKaen Campus, 2022)
The elderly are an important treasure trove of society. Are old people And there is a process of changing according to the nature And the process of continuous change in the final stages of the human age Aging or aging is therefore associated with deterioration. Both physical, mental and behavioral problems and needs of the elderly, there are 5 things 1) physical needs 2) economic needs 3) knowledge needs 4) social needs and 5) psychological needs Then, it is necessary to look after the elderly With this aim, taking care of both body and mind In order to create joint health among the elderly Carers and people in society Therefore presenting Buddhist philosophical concepts in caring for the elderly With the Buddhist principles as follows: 1) Sangahavatthu 4 Dharma is a means to help each other. 2) Brahmavihara 4 is a dharma that helps to support and maintain peace in the coexistence of people in society. 3) The Principle of Sappuris Dharma 7 is the principle of good people. Or the qualities of a good person Those who have studied, know and understand, can apply Will be able to maintain the value of perfect humanity in every respect The care for the elderly on the basis of love and compassion will result in the elderly having a good quality of life, both physically and mentally.